CORONARY ARTERY BYPASS GRAFTING IN POST THYMECTOMY THYMOMATOUSMYASTHENIA GRAVIS PATIENT; A CASE REPORT - Javed, Yasir; Iqbal, Muhammad Afsheen; Janjua, Asif Mehmood; Siddiqi, Rashad; Kirmani, Syed Muzaffar Hasan; Mohsin, Atta; Imran, Muhammad; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2021)
Coronary artery bypass grafting (CABG) in post thymectomy patients of thymomatous myasthenia gravis (MG-T) is a rare procedure. A 42 years old patient with previous thymectomy and chest radiotherapy was in disease remission on pyridostigmine, oral steroids and azathioprine for seventeen years until developed critical diffuse left main stem (LMS) disease. He underwent coronary artery bypass grafting, early extubation, smooth post operative course and was discharged home on 4th post operative day. Optimization for surgery, intraoperative revascularization technique and post operative intensive care management of these patients can be really challenging and require multidisciplinary team effort. Moreover, treatment therapy should be tailored according to severity of symptoms and disease stratification of each individual.